Effect of Sleep on the Attentiveness of Elemetary School Students - K Haynes; K Virgin; M Wilson (Undergraduate Research Journal for the Human Sciences, 2016)
Sleep is known to be important in the development of children and their cognitive functioning. This study worked to establish correlation between amount of sleep and attentiveness in school-aged children. This study surveyed the parents of 10 third graders on their child’s sleep habits. The children were read a story in class and asked to answer questions based on details in the story. The data obtained from this quiz and the parent’s survey responses were then compared to see if there was a relation. The results of this study were inconclusive. When genders were separated, it was found that males slept the most but females got more answers correct on the quiz. However, when the data was organized based on the recommended sleep amount for this age, it was found that children who met the recommendation answered more questions correctly compared to those who did not.
Keywords: Effect; of; sleep; in; school; students